Liquid chromatographic determination and pharmacokinetics study of salbutamol sulphate in rabbit plasma - SUTARIYA, VB; MASHRU, RC; SANKALIA, MG; SANKALIA, JM (Ars Pharmaceutica (Internet), 2006)
To develop and validate a simple, specifi c, precise and accurate HPLC method with UV detection for the determinationof salbutamol sulphate in rabbit plasma. To 0.5 ml of rabbit plasma internal standard (chloramphenicol) was added.Salbutamol sulphate and chloramphenicol were extracted to 5 ml of 0.1 M-bis-(2 ethyl hexyl) phosphate in chloroform.The chloroform phase was treated with 0.5 M hydrochloric acid and an aliquot of the acidic phase was analyzed by areverse phase HPLC system equipped with 4.6 × 250 mm i. d. C18 analytical column and UV detection λ = 276 nm).Mobile phase consisted of water (70%), methanol (20%) and acetonitrile (10%) and its fl ow rate was 1.2 ml/min. Therewere no interfering peaks from endogenous components in blank plasma chromatograms. The drug and internal standardeluted at 3.0 and 15.4 min, respectively. The peak drug/IS area ratio was linear versus drug concentration relationshipwas linear (r=0.992) over 100-1500ng/ml. The extraction effi ciency was greater than 80.00% and minimum quantifi cationconcentration was 100 ng/ml (CV<10%) based on 500ìl of plasma. The intraday coeffi cient of variation (CV) ranged from 1.9 to 6.2% and interday varied from 1.1 to 8.9 %. The % recovery of salbutamol sulphate in plasma range from98.97 to 102.41%. The assay was simple, sensitive, precise and accurate for the use in pharmacokinetic studies of salbutamolsulphate in the rabbit. The mentioned method was used to study the pharmacokinetics of conventional tablets,fast dissolving tablets and fast dissolving fi lm of salbutamol sulphate after oral administration in rabbits